Tacrolimus population pharmacokinetic models according to CYP3A5/CYP3A4/POR genotypes in Chinese Han renal transplant patients. (24th July 2018) - Zhu, Wan; Xue, Ling; Peng, Hongwei; Duan, Zhouping; Zheng, Xuelian; Cao, Duanwen; Wen, Jinhua; Wei, Xiaohua
Aim: To develop a population pharmacokinetic (PK) model of tacrolimus in Chinese Han renal transplant population and establish the influence of different covariates (especially different CYP3A5 / 3A4 / POR genotype) on PK properties.Materials & methods: Trough tacrolimus concentrations, clinical characteristics and CYP3A5/CYP3A4/POR genotypes were collected from 141 adult renal transplant recipients after transplantation. The population PK analysis was carried out using the nonlinear mixed-effect modeling software NONMEM version 3.4.2.Results: Tacrolimus PK profiles exhibited high interpatient variability. A two compartment model with first-order input and elimination described the tacrolimus PK profiles in the studied population. Among the genotypes, only CYP3A5 genotype was confirmed to have clinical significance.Conclusion: Our final model confirmed that CYP3A5*3 plays a more significant role in tacrolimus PK and could affect the blood concentrations and CL/F (clearance rate/bioavailbility). This model is expected to help to improve individualized tacrolimus dosing.